'Life beyond the Walls of my Hometown': Social Safety Networks as a Coping Strategy for Northern Migrants in Accra - Imam, Haruna Abdallah; Tamimu, Hardy (Asian Journal of Social Sciences and Management Studies, 2015)
There is a persistent belief among Northern youth that urban centers, particularly Accra, offer better opportunities for them to improve their lives. These opportunities therefore serve as incentives for them to migrate in large numbers to Accra. However, these migrants are confronted with difficult conditions such as lack of suitable accommodation, lack of regular incomes, high occupational risks, poor remuneration for their services, poor health care, reproductive health problems, and harassment from city authorities among others. Given their high levels of vulnerability within the urban environment, the young migrants, both at the individual and group levels, adopt diverse coping strategies that serve as social safety nets to soften the impact of the harsh socio-economic conditions they encounter in the city. These include accommodation arrangements, job seeking strategies, income management and savings strategies, sources of food and eating habits, health seeking behaviours, disaster management and institutional support. Using mixed methods, this paper explores these social safety nets, and examines the extent to which they have helped improve the well-being of Northern migrants in Sodom and Gomorrah.